2009
DOI: 10.4238/vol8-1gmr549
|View full text |Cite
|
Sign up to set email alerts
|

Heirloom tomato gene bank: assessing genetic divergence based on morphological, agronomic and molecular data using a Ward-modified location model

Abstract: ABSTRACT. Accessions in gene banks need to be characterized and evaluated to determine their genetic diversity. We made a joint diversity analysis of the tomato gene bank of the Universidade Estadual do Norte Fluminense Darcy Ribeiro in Rio de Janeiro State, using the Ward-modified location model. Forty Solanum lycopersicum accessions were characterized and evaluated for 22 morphoagronomic descriptors and 131 random amplified polymorphic DNA markers. Based on the pseudo-F and pseudo-t 2 criteria, the optimal n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
75
0
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(83 citation statements)
references
References 23 publications
2
75
0
6
Order By: Relevance
“…Determining genetic diversity can be based on agronomic, morphological, biochemical, and molecular types of information, among others (Goncalves et al, 2009). Molecular characterization is frequently used by maize breeders as an alternative method for selecting more promising genotypes and reducing the cost and time needed to develop hybrid combinations (Garcia et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Determining genetic diversity can be based on agronomic, morphological, biochemical, and molecular types of information, among others (Goncalves et al, 2009). Molecular characterization is frequently used by maize breeders as an alternative method for selecting more promising genotypes and reducing the cost and time needed to develop hybrid combinations (Garcia et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…According to Gonçalves et al (2009), the logarithmic function of probability precisely defines the number of groups, resulting in less subjective groupings. Different studies have demonstrated that the number of groups can vary greatly depending on the species, the number of accessions, and the type/quantity of variables evaluated (Ortiz et al, 2008;Gonçalves et al, 2009;Barbé et al, 2010;Cabral et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Different studies have demonstrated that the number of groups can vary greatly depending on the species, the number of accessions, and the type/quantity of variables evaluated (Ortiz et al, 2008;Gonçalves et al, 2009;Barbé et al, 2010;Cabral et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Segundo Gonçalves et al (2009) Os oito grupos formados foram constituídos por 36;17;3;13; 25; 22; 16 e 6 acessos (Tabela 1). Para característica coloração da polpa do fruto, os dez acessos que apresentaram coloração branca ficaram alocados nos grupos I, II, IV, V e VIII, enquanto a coloração rosa foi amplamente distribuída em todos os grupos.…”
Section: Resultsunclassified
“…Diversos trabalhos vêm sendo desenvolvidos, utilizando tal procedimento, como, por exemplo, com milho (GUTIÉRREZ et al, 2003;FRANCO et al, 2005;ORTIZ et al, 2008), nabo-forrageiro (PADILHA et al, 2005), tomate (GONÇALVES et al, 2009), feijão (BARBÉ et al, 2010CABRAL et al, 2010), pimenta/pimentão (SUDRÉ et al, 2010) e banana (PESTANA et al, 2011).…”
Section: Introductionunclassified